Advances in Root Canal Therapy: A Systematic Review and Future Perspectives - Wang, Dan (International Journal of Public Health and Medical Research, 2025)
Root canal therapy (RCT) serves as the cornerstone treatment for irreversible pulpitis, pulp necrosis, and periapical lesions. With the integration of digital technology, biomaterials science, and artificial intelligence (AI), the paradigm of RCT has shifted from "infection elimination" to "functional reconstruction" and "tissue regeneration". This systematic review summarizes the latest advances in RCT, focusing on digital diagnostic tools, intelligent treatment systems, novel biomaterials, and regenerative endodontic strategies. We also discuss the current challenges and future directions, aiming to provide a comprehensive reference for clinical practice and scientific research. A literature search was conducted in PubMed, Embase, and Cochrane Library databases using keywords such as "root canal therapy", "digital endodontics", "regenerative endodontics", and "artificial intelligence in dentistry". Relevant studies published between 2018 and 2025 were included, and the final analysis covered 40 high-quality articles (randomized controlled trials, systematic reviews, and prospective cohort studies).